Physical Examination in Patients with Steal Syndrome - Xaviera, Xaviera; Paramita Ayu, Nyoman (Rifa'Institute, 2024)
In Indonesia, the number of haemodialysis (HD) patients is increasing every year. In 2014, there were 17,193 new patients. This number has increased in 2015 as many as 21,050 patients and in 2016 as many as 25,446 patients. HD is a process that involves diffusion and ultrafiltration with the aim of removing certain elements from the blood by taking advantage of the difference in the rate of diffusion of blood as it passes through a semipermeable membrane. HD access is established in the arm by connecting the arm vein with the radial or ulnar artery. Arteriovenous fistula (AVF) is the most ideal HD access, because it can be used for the long term, lower morbidity, and mortality, but complications often occur, one of which is steal syndrome. This syndrome can present with different signs and symptoms depending on the severity and duration of post-access access for renal failure patients undergoing HD therapy